Letters to the editor published in peruvian biomedical journals indexed in SciELO Peru 2006-2013 - Juan José Montenegro-Idrogo; Jhon William Mejía-Dolores; Joel L. Chalco-Huamán (Revista Peruana de Medicina Experimental y Salud Pública, 2015)
This bibliometric study describes the characteristics of letters to the editor published between 2006-2013 in biomedical journals indexed in SciELO-Peru.253 letters (10.3% of total publications) were collected. Most letters (139) were in the Peruvian Journal of Experimental Medicine and Public Health, with marked increase throughout those years. 25% of letters submitted included medical student participation. 14% of authors presented with international affiliations and 27% with endogenous affiliation - common in university journals (Anales de la Facultad de Medicina, Revista Médica Herediana).The usual criteria justifying the publication of letters were: opinion of medical fact or public domain (35.6%) and discussion of results, methodological flaws or interpretation (22.9%). In biomedical journals indexed in SciELO Peru the letters to the editor comprise a percentage of publications that has increased in recent years, with low publication of letters of findings or primary data, compared with opinion or criticism.